Organisational Citizenship Behaviours and job burnout among employees of nonprofit organisations - Bortnowska, Hanna; Seiler, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
Organisational citizenship behaviours (OCBs) are behaviours that go beyond the formal role and are organizationally functional. They may be linked, among others, to job burnout. This relationship has been studied in for-profit and public organisations. No such studies have been found for nonprofit entities operating in different areas.
Keywords: organizational citizenship behaviours; job burnout; nonprofit organizations